2013
DOI: 10.1088/0004-637x/780/2/127
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Third Transient X-Ray Binary in the Galactic Globular Cluster Terzan 5

Abstract: We report and study the outburst of a new transient X-ray binary (XRB) in Terzan 5, the third detected in this globular cluster, Swift J174805.3-244637 or Terzan 5 X-3. We find clear spectral hardening in Swift/XRT data during the outburst rise to the hard state, thanks to our early coverage (starting at L X ∼ 4 × 10 34 ergs/s) of the outburst. This hardening appears to be due to the decline in relative strength of a soft thermal component from the surface of the neutron star (NS) during the rise. We identify … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 128 publications
6
107
2
1
Order By: Relevance
“…We start with the sample of candidate qLMXBs from Heinke et al (2006a), which identified thermally-dominated qLMXBs by spectral fitting, or by hardness ratio plus inferred X-ray luminosity. Analyses of the quiescent behaviour of the outbursting sources Ter 5 X-1 (EXO 1745-248), X-2 (IGR J17480-2446), and X-3 (Swift J174805.3-244637) have been reported in Degenaar, Brown & Wijnands 2011;Degenaar et al 2013;Bahramian et al 2014;Degenaar et al 2015, so we exclude those sources here.…”
Section: Terzanmentioning
confidence: 99%
See 2 more Smart Citations
“…We start with the sample of candidate qLMXBs from Heinke et al (2006a), which identified thermally-dominated qLMXBs by spectral fitting, or by hardness ratio plus inferred X-ray luminosity. Analyses of the quiescent behaviour of the outbursting sources Ter 5 X-1 (EXO 1745-248), X-2 (IGR J17480-2446), and X-3 (Swift J174805.3-244637) have been reported in Degenaar, Brown & Wijnands 2011;Degenaar et al 2013;Bahramian et al 2014;Degenaar et al 2015, so we exclude those sources here.…”
Section: Terzanmentioning
confidence: 99%
“…4 In many previous studies, abundances from Anders & Grevesse (1989) have been used for absorption models. Using these abundances, Bahramian et al (2014) Table 6. Tests of hydrogen (NSATMOS) and helium (NSX) atmosphere models for Terzan 5 CX9.…”
Section: Terzanmentioning
confidence: 99%
See 1 more Smart Citation
“…The flare, with a position consistent with the centre of the globular cluster Terzan 5, was detected by INTEGRAL (Bordas et al 2010) and allowed the discovery of the new accreting pulsar IGR J17480-2446 (Papitto et al 2011). The second brightest flare in Terzan 5 peaked on 2012 July 18 and corresponds to a Type-I burst, which led to the discovery of the new accreting neutron star Terzan 5 X-3 (Bahramian et al 2014). …”
Section: Terzan 5 and Igr J17480-2446mentioning
confidence: 96%
“…On the other hand, it is proposed from the analysis of the photospheric radius expansion that an accretion rate may change during the burst by some factors [21]. Changes in accretion rates are also considered from recent study of the outburst of a transient X-ray binary [22]. Therefore, it is reasonable to include accretion rate variations in numerical calculations because the observations indicate that the luminosity of accreting neutron stars is variable.…”
Section: Introductionmentioning
confidence: 99%